The Role of Multichannel Marketing in Customer Retention and Loyalty: Study in Emerald Bank Customer in Indonesia - Ambarwati, Ambarwati; Hadiwidjojo, Djumilah Zain; Sudiro, Achmad; Rohman, Fatchur (Department of Management, Faculty of Economics and Business, Brawijaya University, 2014)
Attention on the relationship between customer retention, customer loyalty, and customer satisfaction that serves as